2007
DOI: 10.1042/ba20070044
|View full text |Cite
|
Sign up to set email alerts
|

Sf‐Caspase‐1‐repressed stable cells: resistance to apoptosis and augmentation of recombinant protein production

Abstract: Sf-Caspase-1 [Spodoptera frugiperda (fall armyworm) caspase-1] is the most studied effector caspase of Lepidoptera and its activation may lead cells to apoptosis (programmed cell death) when under UV irradiation or baculovirus infection. In the present study, we repressed the expression of Sf-caspase-1 in Sf9 (S. frugiperda 9) cells using constitutive RNA interference, and evaluated the effects of stress responses and the production of proteins in recombinant baculovirus-infected cells. The Sf-caspase-1-repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…These results demonstrated that Sf -caspase-1 mRNA was successfully suppressed by Sf -caspase-1 dsRNA in both Sf9/pIBdsCasp-1 and Sf9/pIBdsCasp-2 cells. In our previous study, we tested the expression of P35, a substrate inhibitor of Sf -caspase-1, in Sf9/pIBdsCasp-1 and Sf9/pIBdsCasp-2 cells, and found that the level of P35 in pIBdsCasp transfected cells was evidently higher than that found in normal cells [25]. Thus, we suggested that Sf -caspase-1 is suppressed in these Sf -caspase-1-repressed cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These results demonstrated that Sf -caspase-1 mRNA was successfully suppressed by Sf -caspase-1 dsRNA in both Sf9/pIBdsCasp-1 and Sf9/pIBdsCasp-2 cells. In our previous study, we tested the expression of P35, a substrate inhibitor of Sf -caspase-1, in Sf9/pIBdsCasp-1 and Sf9/pIBdsCasp-2 cells, and found that the level of P35 in pIBdsCasp transfected cells was evidently higher than that found in normal cells [25]. Thus, we suggested that Sf -caspase-1 is suppressed in these Sf -caspase-1-repressed cells.…”
Section: Resultsmentioning
confidence: 99%
“…Stable cells (Sf9/pIB, Sf9/pIBdsCasp-1, and Sf9/pIBdsCasp-2 cells) were established by transfection of the control vector pIB or vector pIBdsCasp (Figure 2), and subsequently selected by BSD [25]. After more than 20 passages, stable cell lines were analyzed by genomic DNA PCR and RT-PCR to examine the inverted-repeat DNA sequence of Sf -caspase-1 and endogenous expressed Sf -caspase-1 mRNA quantity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations